CENTRAL AUDITORY PROCESSES PREDICT READING ABILITIES OF CHILDREN WITH DEVELOPMENTAL DYSLEXIA. - Lewandowska, Monika; Gane, Malgorzata; Wlodarczyk, Elzbieta; Senderski, Andrzej; McPherson, David L.; Bednarek, Dorota; Skarzynski, Henryk (Journal of Hearing Science, 2013)
Background: In this paper we showed predictive relationships between central auditory processes, phonological abilities, and reading abilities in children diagnosed with developmental dyslexia (DD). Both empirical data and theoretical approaches indicate that central auditory processing deficits may contribute to developmental dyslexia; however, associations between reading and phonological skills and central auditory processes remain unclear. Material and methods: Exactly 57 children with dyslexia and 40 age- and gender-matched normal reading children performed reading, phonological, and auditory information processing tests, i.e. the Frequency Pattern Test (FPT), Dichotic Digit Test (DDT), and Gap Detection Test (GDT). Results: Dyslexic children showed parallel reading, phonological, and auditory information processing deficits. Principal component analysis, performed in dyslexic and normal reading children to reduce the data set before exploring the predictors of language skills, revealed three factors: 1) 'Auditory processing', which received high loadings from phonological, FPT, and DDT for the right ear; 2) Age and Cognition, including chronological age as well as measures of fluid intelligence and auditory working memory span; and 3) 'Dichotic listening' for the left ear. All three factors together best predicted reading regular words in children diagnosed with DD, while Auditory processing' and Age and cognition' together explained most of the variance while predicting pseudo-word reading. Conclusion: The present study indicates that frequency pattern recognition, dichotic listening for the right year, and phonological awareness are strongly interrelated and constitute the most significant predictor of reading abilities in children diagnosed with dyslexia. The results may have important implications for diagnosis and therapy of language disorders.